Integrating Religious Character and Science Education at SMK KHAS Kempek: A Qualitative Study on Holistic Educational Approaches in Indonesia - Mintarsih Danumiharja; Fathurohman, Oman; Subasman, Iman; Nugraha, Firman; Hamdun, Ibnu (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study explores the integration of religious character education with science education at SMK KHAS Kempek, Cirebon, highlighting the necessity for a holistic educational approach that fosters both moral and academic competencies in students. The research aims to fill the gap between theoretical frameworks and practical implementation in character education, by focusing on the integration of religious and scientific values within a modern educational setting. Design/methods/approach – employing a qualitative and descriptive methodology, this study involved field research at SMK KHAS Kempek, combining interviews, participative observations, and documentary analysis. Primary data was collected through interviews with school administrators, teachers, and students, while secondary data was gathered from academic journals and online articles relevant to religious character and science education. Findings – The results indicate that the integrated educational model at SMK KHAS Kempek is effective in enhancing both the moral and intellectual development of students. The study found that religious teachings integrated with scientific concepts help create a learning environment conducive to both spiritual and empirical understanding. This approach not only aligns with national educational goals but also provides a framework that can be adapted by other educational institutions in Indonesia. Research implications – This study suggests that other Indonesian educational institutions can adopt a similar integrated educational model to achieve comprehensive character development and effective scientific learning. However, further research is needed to understand the broader application of this approach in different educational contexts.